The Impact of Parent-child Sports Games on Children's Psychological Development - Zhao Fang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Childhood is a stage of rapid psychological development, movement and psychological development are inseparable. At this stage, games are the main form of activity for children which play a dominant role in promoting children's psychological development. By implementing parent-child sports game intervention activities, children can prevent psychological disorders or behavioural problems, help them better adapt to social life, and make more effective contributions to society and humanity. Therefore, current research aimed to check the impact of parent-child sports games on children's psychological development. For this purpose, survey subjects were 50 students from large class of kindergarten A and 50 students from the large class of kindergarten B. An experimental research design was applied by using control and experimental group. The findings that the experimental group showed significant improvements in cognitive ability, emotional stability, willpower, and personality shaping compared to the control group. Moreover, their social adaptability was notably higher, fostering smoother communication and harmonious interpersonal relationships. The findings highlight the importance of early engagement in sports game activities to promote psychological health and resilience in preschool children, emphasizing the need for integrating such activities into early childhood education and parental involvement programs. The research also explored a new research area for further research.